Pengaruh Job Insecurity dan Workload Terhadap Job Performance Karyawan Sebuah Resort di Tabanan - Artajaya, Made; Lindisari, Komang Indah (Stupa, 2024)
Job performance is the primary issue at WakaGangga Resort Tabanan. The decline in job performance is evident from the job performance appraisal, which indicates that employees cannot perform their tasks optimally. The author broadly identifies the main causes of this issue as employees feeling insecure about their jobs and experiencing excessive workloads. This study was conducted at WakaGangga Resort Tabanan. The data analysis method used in this research is multiple linear regression, with questionnaires distributed to 50 employees. The sampling technique employed is the saturated sampling technique. The results of this study indicate that job insecurity has a significant partial effect on job performance. Similarly, workload also has a partially significant impact on job performance. Furthermore, both job insecurity and workload have a significant simultaneous effect on job performance.